KONSEP PENDIDIKAN ISLAM BERDASARKAN AL-QURAN AL-KARIM - Muhammad Arif (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The concept of education in the Qur’an is the best educational concept in the world. It is because the Qur’an is a revelation of God. Education of the Qur’an is a guidance for humans beings to be happy and safe in the world and the hereafter. The concept of education has succeeded in giving birth to the best human generation. They are the generation that the Prophet guided by guidance of the Qur’an. So that the succees is re-realized then the concept of education in the Qur’an should be applied.